Regulators, functions, and mechanotransduction pathways of matrix stiffness in hepatic disease - Guo, Ting; Wantono, Cindy; Tan, Yuyong; Deng, Feihong; Duan, Tianying; Liu, Deliang (Frontiers in Physiology, 2023)
The extracellular matrix (ECM) provides physical support and imparts significant biochemical and mechanical cues to cells. Matrix stiffening is a hallmark of liver fibrosis and is associated with many hepatic diseases, especially liver cirrhosis and carcinoma. Increased matrix stiffness is not only a consequence of liver fibrosis but is also recognized as an active driver in the progression of fibrotic hepatic disease. In this article, we provide a comprehensive view of the role of matrix stiffness in the pathological progression of hepatic disease. The regulators that modulate matrix stiffness including ECM components, MMPs, and crosslinking modifications are discussed. The latest advances of the research on the matrix mechanics in regulating intercellular signaling and cell phenotype are classified, especially for hepatic stellate cells, hepatocytes, and immunocytes. The molecular mechanism that sensing and transducing mechanical signaling is highlighted. The current progress of ECM stiffness’s role in hepatic cirrhosis and liver cancer is introduced and summarized. Finally, the recent trials targeting ECM stiffness for the treatment of liver disease are detailed.